Relationship between neurological complications, cerebrovascular and cerebral perfusion following off-pump coronary artery bypass grafting. (20th May 2015) - Xu, Baolei; Qiao, Qiubo; Chen, Mingying; Rastogi, Radhika; Luo, Di; Bi, Qi
Abstract : Objective: To investigate risk factors for neurological complications after off-pump coronary artery bypass grafting (OPCABG). Methods: We reviewed the cases of 813 patients who underwent OPCABG between August 2010 and September 2013.Data from preoperative 320 dynamic volume computed tomography (CT), CT angiography (CTA), CTA perfusion, and cerebrovascular function examinations were assessed. Neural function was assessed before and 7 days after operation, and patients were assigned to either the neurological complications or non-neurological complications group. Results: Neurological complications were observed in 23.4% (190/813) of patients; cerebral infarction in 1.1% (9/813); hypoxic ischemic encephalopathy in 2.3% (19/813); delirium in 1.5% (12/813); postoperative cognitive dysfunction in 12.9% (105/813); and anxiety/depression in 8.2% (67/813). Patients in the neurological complications group were older, were more likely to have a previous history of cerebrovascular disease and diabetes, had more severe extra-cranial carotid artery stenosis, had more severe stenosis on CTA, and had more perfusion abnormalities compared to patients in the non-neurological- complications group ( P < 0.05). Logistic regression analysis identified the following independent risk factors for neurological complications: male gender (odds ratio [OR], 1.816; 95% confidence interval [CI], 1.017–3.244; P = 0.044); cerebrovascular disease history (OR, 1.837; 95% CI, 1.075–3.141; P = 0.026); and perfusion abnormalities (OR, 3.224; 95% CI, 2.073–5.013; P = 0.000). Occipital lobe cerebral blood flow (CBF); differences in temporal lobe, occipital lobe, and basal ganglial time to peak (TTP); and the difference in occipital lobe and basal ganglial mean transit time (MTT) were significantly higher in the neurological complications group ( P < 0.05). For the TTP difference, the area under the receiver operating characteristic (ROC) curve was 0.606. Discussion: Neurological complications were observed in 23.4% of patients following OPCABG. Male gender, cerebrovascular disease history, and perfusion abnormalities were independent risk factors for neurological complications. Temporal lobe TTP on CTA perfusion was the best predictor of neurological complications.